Chapter 6 Textures of urban fears : The affective geopolitics of the ‘oriental rug’ (2020)
We will discuss in detail the two exhibitions and their vicissitudes in the paragraphs to come, focusing on the emotional public reactions they both evoked, albeit to different degrees.